Factors associated to the cicatrization success of lower-limb ulcer of venous etiology (2018)
ABSTRACT: Objective: The study sought to establish the relationship among the sociodemographic and clinical factors with cicatrization success in patients with lower-extremity ulcers of venous etiology (UVE). Methods: Multi-center, prospective cohort study with participation of 80 patients with UVE assessed in three clinics from the city of Medellín (Colombia). Sociodemographic conditions were characterized and the clinical characteristics of the wounds evaluated with the Resvech 2.0 scale. Results: The work showed that 48.7% of the patients (52.5% of the women and 38.1% of the men) had cicatrization success of the lesion during a maximum time of 90 days. The Cox proportional risk model showed that cicatrization time was higher in patients belonging to low socioeconomic level (HR = 2.0), with lesions of greater compromise (HR = 2.7), and who were treated by nurses with experience <5 years (HR = 2.1). Conclusion: The factors associated with cicatrization success of ulcers of venous etiology are: belonging to socioeconomic levels above two (on a scale from 1 to 6), with a slight lesion, and the nursing staff treating the patient having five or more years of experience in the treatment of wounds. Promotion should take place for nurses to be trained on these themes and on improving their expertise, given that this is a factor that can be modified and which indicates the success of the cicatrization of these lesions.